Chimeric Antigen Receptor-Modified T Cell Therapy in Multiple Myeloma: Beyond B Cell Maturation Antigen - Timmers, Marijke; Roex, Gils; Wang, Yuedi; Campillo-Davo, Diana; Van Tendeloo, Viggo F. I.; Chu, Yiwei; Berneman, Zwi N.; Luo, Feifei; Van Acker, Heleen H.; Anguille, Sébastien (Frontiers in Immunology, 2019)
Chimeric antigen receptor (CAR)-modified T cell therapy is a rapidly emerging immunotherapeutic approach that is revolutionizing cancer treatment. The impressive clinical results obtained with CAR-T cell therapy in patients with acute lymphoblastic leukemia and lymphoma have fueled the development of CAR-T cells targeting other malignancies, including multiple myeloma (MM). The field of CAR-T cell therapy for MM is still in its infancy, but remains promising. To date, most studies have been performed with B cell maturation antigen (BCMA)-targeted CARs, for which high response rates have been obtained in early-phase clinical trials. However, responses are usually temporary, and relapses have frequently been observed. One of the major reasons for relapse is the loss or downregulation of BCMA expression following CAR-T therapy. This has fostered a search for alternative target antigens that are expressed on the MM cell surface. In this review, we provide an overview of myeloma target antigens other than BCMA that are currently being evaluated in preclinical and clinical studies.